Exploration of the Project to Strengthen the Profile of Pancasila Students in Islamic Education - Qulyubi, Mujib; Komara, Endang (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to explore the role of the Pancasila Student Profile Strengthening Project (P5) as a means of achieving student character through Pancasila values. Through literature studies, this study examines how applying P5 provides opportunities for students to experience knowledge as a process of strengthening character and utilizing the surrounding environment as a learning resource. The Pancasila student profile dimension emphasizes that education focuses on cognitive abilities and students' attitudes and behaviors as citizens of Indonesia and the world. Educators are important in helping students grow their capacity and build noble morals to the Pancasila student profile. In addition, Islamic education plays a central role in shaping the character of the young generation with noble character, in addition to social and environmental factors, media influence, and government policies. Thus, Islamic education is a key element in producing a young generation that is qualified and moral by the values of Pancasila.